Inteligencia de negocios aplicada al uso de recursos en la producción de acero - Tigselema Egre, Suanny Gabriela (2024)
The steel industry in Ecuador faces significant challenges with respect to resource consumption and unplanned production interruptions. Uncontrolled resource consumption increases operating costs and equipment wear, which can result in production interruptions and economic losses. This study focuses on an Ecuadorian steel company. The company seeks to improve sustainability and reduce its environmental impact, which requires efficient resource management. Efficient resource management requires informed decision making. This project used business intelligence solutions combined with data analysis to identify the most common causes of production interruptions, trends related to fuel consumption and carbon dioxide (CO2) emissions. The project provides knowledge on data analysis techniques applicable to the steel industry, especially in terms of resource management. It provides the steel company with key information for strategic decision making, enabling the creation of plans for the mitigation of production interruptions. This knowledge can also be valuable for other companies in the sector seeking to optimize their processes and resources.